Perspectives of entrepreneurship in engineering education: an exploratory study - Leão, Celina Pinto (2019)
Entrepreneurship relevance is recognized and the governments investments are visible through the startup programs volume that have been arising all over the world. Universities can promote the entrepreneurial spirit and help to develop entrepreneurship skills in their engineering students. This could increase engineering students intentions to create their own business or to be intrapreneurs in the employee companies, helping the development of their future careers. This work is the result of the first intervention of the authors on engineering schools. A survey was distributed to engineerings students and young professionals in order to analyse their entrepreneurship perspectives. Early findings show that students should learn more about entrepreneurship, however, opposing results were obtained related with how these issues should be addressed in an engineering course. This on going work covers important topics that need a more detailed analysis.